Anthropogenic influence on the water resource quality in the village of Bălănești, Nisporeni district - Melentiev, Eugenia; Rotaru, Mirela (Acta et Commentationes Exact and Natural Sciences, 2023)
Water is one of the fundamental elements of life, and, at the same time, the factor that defines social-economic development. That is why the current state of water resources is a pressing and current problem of contemporary society. The evaluation of the anthropogenic impact on some water sources in the village of Bălănești, Nisporeni district, highlighted the real state of the surface and underground waters in this area by determining some physico-chemical quality indices; establishing the correlation of the content of some main ions (Ca+2, Mg2+, Cl-, SO42-, HCO-3) with the content of nitrates as well as determining the degree of pollution of the Nârnova River.